ASSESSING THE LOCAL COMMUNITY READINESS TO SUNDA STRAIT BRIDGE DEVELOPMENT PLAN - Hayati, Cucu (Media Mahardhika, 2018)
The objective of this study is to identify how Sunda Strait Bridge will affect to local community readiness. It also investigated the adaptive capacity of stakeholders related to Sunda Strait Bridge Development Plan. This research was began by collecting quantitative preliminary data as a basis for collecting and interpreting the primary qualitative data. In order to obtain representative responses, this research used purposive sampling technique. The number of respondents of this research were 100 people from different interests who live in Pulomerak Districts, Ciwandan Districts, Grogol Districts and Citangkil Districts. This research’s process divided into three stages, stages of preparation/ pre-field (description about the research and make analogy with related researches), stages of field work (classifying responses and adaptive capacity), and stage of post field work (connecting between theory and finding). It can be concluded that Sunda Strait Bridge is not relevant to be built today because the community is not ready yet. In the other hand, the objective of Sunda Strait Bridge Development Plan would be supported by community readiness and community-personal adaptation, even it could not address the issues of negative impacts. This research gives three kind recommendations to intervention for policy and planning to minimize the residue and local community adaptation strategy.